BUDAYA PESISIRAN DAN PEDALAMAN DALAM TAFSIR AL-QUR’AN (Studi Kasus Tafsir al-Ibrīz dan Tafsir al-Huda) - Imam Muhsin (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2014)
AbstractCommentary of al-Ibrīz and commentary of al-Huda are the twocommentaries of the Qur'an that accommodate the local culture, particularly inJava. Culture accommodation occurs mainly in the realm of language, namely Java language. It is because language as the instrument of articulation to transfer cultural values. In addition, Javanese language also used in al-Ibrīz commentary and al-Huda commentary. The usage of Javanese language in everycommunication always need cultural values which is articulated and stated to the reader through the interpretation of God statements in Qur’an with the complex and unique method. It is also used tricky psycho-cultural aspect. The differences of cultural accommodation from the both of two books of commentary and consistency in using Javanese cultural concepts, depth discussion in linking values or concepts of Javanese culture, as well as compliance with the application of the values of Javanese culture. Al-Ibrīz commentary where the author was born in the coastal area of Java tend to be inconsistent, the discussion is not exhaustive, and less adhere to the applicationof Javanese cultural values. While the al-Huda commentary which is the writer has Javanese cultural background inland tend to be consistent, deep, and adherence to social values and culture in the Java community.Keywords: al-Ibrīz commentary, al-Huda commentary, Javanese culture.